Numerical Simulation and Optimization Design of End-Suspended Pile Support for Soil-Rock Composite Foundation Pit - Qingchao Xu; Zhenhao Bao; Tu Lu; Huarui Gao; Jiakang Song (Advances in Civil Engineering)
In order to design the soil-rock combination foundation pit more safely and effectively, this paper presents the investigations of the mechanical and deformational characteristics of end-suspended piles supporting the structures in Jinan CBD area. Based on the measured data, a finite element model was established through the two-dimensional numerical simulation method to study the deformational characteristics of the end-suspended piles, and the influences of the depth of socketed rock, the width of rock shoulder, and the prestress of anchor cables on the deformations and mechanical property of end-suspended piles were discussed. Some optimization methods are proposed based on these analyses. Results show the following: (1) Rock-socketed depths have boundary effect on end-suspended piles. Under the given geological conditions, the reasonable socketed ratio is within 0.158∼0.200. (2) The anchor cable prestress can effectively slow down the ground settlement, the force, and deformation of the pile body and can be set to 1P∼1.25P under the conditions of the site. (3) Rock-shoulder width has little influence on the ground settlement and horizontal displacement of piles. The reserved width of rock shoulder is suggested to be selected in the range of 1.0 m∼1.5 m.